ALE meta-analysis workflows via the BrainMap database: progress towards a probabilistic functional brain atlas - Laird, Angela R.; Eickhoff, Simon B.; Kurth, Florian; Fox, Peter M.; Uecker, Angela M.; Turner, Jessica A.; Robinson, Jennifer L.; Lancaster, Jack L.; Fox, Peter T. (Frontiers in Neuroinformatics, 2009)
With the ever-increasing number of studies in human functional brain mapping, an abundance of data has been generated that is ready to be synthesized and modeled on a large scale. The BrainMap database archives peak coordinates from published neuroimaging studies, along with the corresponding metadata that summarize the experimental design. BrainMap was designed to facilitate quantitative meta-analysis of neuroimaging results reported in the literature and supports the use of the activation likelihood estimation (ALE) method. In this paper, we present a discussion of the potential analyses that are possible using the BrainMap database and coordinate-based ALE meta-analyses, along with some examples of how these tools can be applied to create a probabilistic atlas and ontological system of describing function-structure correspondences.